PEMERIKSAAN ELEKTRONEUROGRAFI SEBAGAI PENILAIAN NEUROPATI PERIFER PADA PEKERJA TERPAPAR VIBRASI - Alifa Dimanti*, Fitri Octaviana**, Jofizal Jannis**, Joedo Prihartono*** (NEURONA, 2009)
BACKGROUND LONG TERM EXPOSURE TO VIBRATION MAY CAUSE PERSISTENT SENSORINEURORAL DISORDERS AS WELL AS VASCULAR AND MUSCULOSKELETAL DISORDERS ELECTRONEUROGRAPHIC ENG EXAMINATION IS A GOLD STANDARD TO EVALUATE PERIPHERAL NEUROPATHY DUE TO VIBRATION EXPOSURE IN EARLY PHASE HENCE IT CAN BE USED AS AN EARLY DETECTION BEFORE CLINICAL MANIFESTATION OCCURS